Efficacy of the BOPPPS teaching model in enhancing end-of-life care education and attitudinal outcomes among Chinese nursing students - Xu, Qiu Zhu; Chen, Junxi; Xu, Qiusui; Zhang, Jiali; Yang, Yingzi (Frontiers in Education, 2025)
ObjectiveThis study evaluated the efficacy of the Bridge-in, Objective, Pre-test, Participatory Learning, Post-test, Summary (BOPPPS) teaching model in improving the knowledge, skills, and attitudes of nursing students on end-of-life care.MethodsThe students enrolled in the fourth year of the 2021 nursing technology program were divided into control (n = 173) and experimental (n = 180) groups. The control group was taught using the traditional method for end-of-life care, and the experimental group was instructed using the BOPPPS method. Standard validated questionnaires, namely Frommelt Attitude Toward Care of the Dying Scale Form B (FATCOD-B) and Templer’s Death Anxiety Scale (T-DAS), were used to measure the attitudes of the students and their emotional responses to end-of-life care following the course. Test–retest was used to assess the reliability of the questionnaires. The academic performance of the students was determined using written and skill-based assessments. Semi-structured interviews were conducted with 12 experimental group participants to obtain qualitative feedback on the BOPPPS instruction. The interviews were audio-recorded, transcribed, and analyzed thematically.ResultsBoth the FATCOD-B (Cronbach’s α = 0.891) and T-DAS (Cronbach’s α = 0.943) had a high internal consistency. Compared to the control group, the experimental group showed significantly higher FATCOD-B scores (89.21 ± 4.96 vs. 87.82 ± 5.29, p < 0.01), T-DAS scores (32.66 ± 9.23 vs. 30.04 ± 9.05, p < 0.01), and total academic scores (90.36 ± 14.45 vs. 81.97 ± 19.77, p < 0.001). The thematic analysis revealed three key benefits of the BOPPPS instruction method: enhanced pre-class engagement, reduced apprehension in terminal care, and improved critical thinking with knowledge internalization.ConclusionThe BOPPPS instructional framework effectively optimizes hospice care education by simultaneously developing nursing students’ knowledge acquisition, clinical skills, and professional attitudes, thereby better preparing them for end-of-life care challenges.